Perancangan Identitas Brand Parfum Freia Untuk Membangun Rekognisi Brand Dengan Metode Design Thinking Pada Target Audiens Umur 18-35 Tahun Di Shopee - Setyoraharjo, Pantaleon; Nirwana, Aditya; Prasetya, Bintang Pramudya Putra (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2023)
Sales of cosmetics coupled with the popularity of online stalls have created new trends in beauty products. This trend was capitalized on by Freia to start his new business. But with so many kinds of perfume brands and their subjectivity, a consistent visual identity and communication is needed that can communicate Freia's unique values and concepts. From that Freia can be distinguished from other brands. That is the medium chosen for Freia to build brand recognition so that it can be recognized and differentiated from competitors. The method used is Design Thinking from the book Design Thinking Playbook by Michael Lewrick, Patrick Link and Larry Leifer. Methods of data collection using qualitative methods according to Patricia Leavy. With this method, holistic research and collaborative flow design can be carried out to attract varied and subjective perfume designs. In research, from the results of the analysis, a new Freia brand identity will be generated which is contained in a Graphic Standard Manual consisting of brand concepts, brand values, logos, slogans, color palettes, typography, graphic assets and their implementation designs on packaging, signs, stationery, media social, exhibition, vehicle and uniform. After testing the responses from the sources, Freia's brand identity can be communicated and Freia is not associated with other brands.